RANCANGAN MODEL PELATIHAN SUMBER DAYA MANUSIA BERBASIS E-TRAINING DALAM RANGKA IMPLEMENTASI LEARNING ORGANIZATION (ORGANISASI PEMBELAJAR) - Suci Pratiwi (Jurnal Manajemen Pendidikan, 2016)
The purpose of this study was to analyze, plan, develop and test a training model based on electronic training (e-training) in PT Drife Solusi Integrasi. This study adapting research and development method by borg and gall with six steps start from research and information collecting, planning, Develop Preliminary of Product, preliminary field testing,main product revision until main field testing. Results of this study is a training model basedon electronic training (e-training) suitable for startup companies.